1999
DOI: 10.1007/pl00012330
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rate of Cholecystectomy after Introduction of Laparoscopic Cholecystectomy in Saudi Arabia

Abstract: A rapid increase in the rate of cholecystectomy was reported in eastern Saudi Arabia between 1977 and 1986. The aim of this study was to determine whether the rate of cholecystectomy in the same region was still rising after the introduction of laparoscopic cholecystectomy. From 1987 to 1995 a total of 24 hospitals in eastern Saudi Arabia were surveyed using a questionnaire. During the 9-year study period, the rate of total cholecystectomy (open and laparoscopic) increased by 91%. Whereas the cholecystectomy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…One change that has been noted in many centers is an apparent increase in the number of cholecystectomies performed since the start of the laparoscopic era [1,6,12,19]. This reported increase has varied significantly: Lam et al [12] described an increase of 18.7% between 1989 and 1993 in Scotland, whereas a study of patients in New York by Legoretta et al [13] found an increase of 57% between 1988 and 1992.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One change that has been noted in many centers is an apparent increase in the number of cholecystectomies performed since the start of the laparoscopic era [1,6,12,19]. This reported increase has varied significantly: Lam et al [12] described an increase of 18.7% between 1989 and 1993 in Scotland, whereas a study of patients in New York by Legoretta et al [13] found an increase of 57% between 1988 and 1992.…”
Section: Discussionmentioning
confidence: 89%
“…Several centers have reported an increase in the cholecystectomy rate since the introduction of the laparoscopic technique [1,4,6,12,15]. There are a number of possible explanations for this reported increase.…”
mentioning
confidence: 88%
“…[27] Previous reports from our institution have indicated that early LC for AC is safe, with a low rate of conversion to open cholecystectomy, few complications, and no mortality. [128]…”
Section: Discussionmentioning
confidence: 99%
“…2 This has occurred despite a lack of evidence that gallstone incidence has increased to the same degree. Laparoscopic cholecystectomy has a lower mortality rate than open cholecystectomy, but in view of the increased cholecystectomy rate, there may be no decrease in the total number of deaths associated with this operation 1.…”
mentioning
confidence: 99%